2021
DOI: 10.1111/febs.16099
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 recruitment, activity, and function in organelles

Abstract: Protein coding mutations in Leucine-rich repeat kinase 2 (LRRK2) cause familial Parkinson's disease (PD) and non-coding variations around the gene increase the risk of developing sporadic PD. It is generally accepted that pathogenic LRRK2 mutations increase LRRK2 kinase activity, resulting in a toxic hyperactive protein that is inferred to lead to the PD phenotype. LRRK2 has long been linked to different membrane trafficking events, but the specific role of LRRK2 in these events has been difficult to resolve. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 162 publications
0
45
0
Order By: Relevance
“…While it remains unclear how LRRK2 drives PD, LRRK2 has been functionally linked to membrane trafficking [12][13][14] . Mutant LRRK2 causes defects in endo/lysosomal, autophagosomal, and mitochondrial trafficking [15][16][17][18][19] , and LRRK2 regulates lysosomal morphology [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it remains unclear how LRRK2 drives PD, LRRK2 has been functionally linked to membrane trafficking [12][13][14] . Mutant LRRK2 causes defects in endo/lysosomal, autophagosomal, and mitochondrial trafficking [15][16][17][18][19] , and LRRK2 regulates lysosomal morphology [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…A subset of Rab GTPases, which are master regulators of membrane trafficking 27 , are phosphorylated by LRRK2, and PD-linked LRRK2 mutations increase Rab phosphorylation in cells 9,28 . Phosphorylation of Rabs by LRRK2 is linked to alterations in ciliogenesis [25][26][27] and defects in endolysosomal trafficking 14 . LRRK2 also co-localizes with microtubules in cells and in vitro [29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…LRRK2 phosphorylates itself at Serine 1292 (Sheng et al 2012) as well as Serine/Threonine residues in a conserved region of the switch II domain of a subset of Rab GTPases, leading to differential interactions with effector proteins and thus linking LRRK2 to vesicle mediated transport (Steger et al 2016;Bonet-Ponce and Cookson 2019). Likely due to the phosphorylation of Rab GTPases, LRRK2 has been nominated to play important roles at endomembranes including early endosomes, recycling endosomes, late endosomes, and lysosomes (Roosen and Cookson 2016;Hur et al 2019;Yun et al 2015;Bonet-Ponce and Cookson 2021). We and others have previously shown that damage to membranes within the endolysosomal system results in LRRK2 activation as measured by Rab phosphorylation (Bonet-Ponce et al 2020;Herbst et al 2020;Eguchi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the most common causes of familial PD are mutations in leucine-rich repeat kinase 2 ( LRRK2 ), and this is a strong risk factor for sporadic disease [ 30 ]. This is a large multi-domain protein (280 kDa) with a GTPase domain, serine/threonine kinase domains, and other domains involved in protein–protein interactions [ 31 ]. This kinase interacts with many molecules, including Rab GTPases.…”
Section: Introduction To Pd Pathogenesismentioning
confidence: 99%
“…Mutations in these domains may lead to a hyperactive protein with toxic effects. LRRK2 plays multiple roles in cells, including in vesicular trafficking, endosomal transport, autophagy, cytoskeleton dynamics, ciliogenesis, neurite growth, mitochondrial morphology, and mitochondrial calcium regulation [ 31 , 32 , 33 , 34 , 35 ]. In nigral neurons, it is specifically involved in vesicle formation and docking, as well as ER-to-Golgi and Golgi-to-membrane transport and the internalization of dopamine receptors at the synapse [ 36 , 37 ].…”
Section: Introduction To Pd Pathogenesismentioning
confidence: 99%